Analisis Kinerja Pelayanan Rawat Inap Antar-Bangsal dengan Kombinasi Algoritma AHP dan SAW - Farel Dani Arfiyan; R. Rhoedy Setiawan; Anteng Widodo (Politeknik Ganesha Medan, 2026)
Evaluation of hospital service quality is a crucial instrument for continuously improving the quality of public healthcare services. Although patient satisfaction surveys have been conducted periodically, the collected assessment data have generally not been optimally utilized as the basis for evaluating the performance of inpatient wards. This study aims to implement a Decision Support System (DSS) to analyze the performance of inpatient wards objectively, measurably, and comparatively. A hybrid approach was employed by integrating the Analytic Hierarchy Process (AHP) algorithm to determine the weights of six service quality criteria, namely administrative services, medical competence and responsiveness, staff friendliness, inpatient room facilities, environmental cleanliness and comfort, and information and communication, with the Simple Additive Weighting (SAW) method to calculate the ranking of alternatives. To ensure a fair evaluation, the analysis was divided into two categories, namely VIP/VVIP wards and regular wards. The results indicate that Fresia 5 achieved the highest preference value in the regular ward category with a score of 0.9155, while Edelweiss 4 (VVIP) obtained the highest preference value in the VIP/VVIP category with a score of 1.0000. The system also successfully identified six wards while demonstrating stable ranking results through sensitivity analysis of changes in criteria weights. The computational results were integrated into a web-based dashboard to visualize ward rankings interactively. The combination of the AHP and SAW algorithms proved effective in processing multicriteria assessments and reducing subjective bias. The findings facilitate hospital management in mapping unit performance more efficiently to support service quality improvement. In conclusion, the integration of both algorithms produces valid and consistent decision recommendations that can be used to determine priorities for improving hospital service quality.